Nekrolog zakonny jako tekst tożsamościowy = Monastic obituaries as identity texts - Borkowski, Igor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author proposes a definition of an identity text and, through an analysis of collections of obituaries of deceased monastic sisters, distinguishes characteristic features, types and functions of such texts. The fundamental roles of an identity statement are: informing, persuading, image building and evoking a sense of pride in belonging to a group, as well as launching group interaction mechanisms.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie